Pre‐transplant soluble CD30 in combination with total DSA but not pre‐transplant C1q‐DSA predicts antibody‐mediated graft loss in presensitized high‐risk kidney transplant recipients1. (3rd February 2016) - Schaefer, S. M.; Süsal, C.; Opelz, G.; Döhler, B.; Becker, L. E.; Klein, K.; Sickmüller, S.; Waldherr, R.; Macher‐Goeppinger, S.; Schemmer, P.; Beimler, J.; Zeier, M.; et al.
Abstract: Presensitized kidney transplant recipients are at high‐risk for early antibody‐mediated rejection. We studied the impact of pre‐ and post‐transplant donor‐specific human leukocyte antigen (HLA) antibodies (DSA) and T‐cell‐activation on the occurrence of antibody‐mediated rejection episodes (AMR) and graft loss (AMR‐GL) in a unique cohort of 80 desensitized high‐risk kidney transplant recipients. Patients with pre‐transplant DSA demonstrated more AMR episodes than patients without DSA, but did not show a significantly increased rate of AMR‐GL. The rates of AMR and AMR‐GL were not significantly increased in patients with complement split product (C1q)‐binding pre‐transplant DSA. Pre‐transplant C1q‐DSA became undetectable post‐transplant in 11 of 13 (85%) patients; 2 (18%) of these 11 patients showed AMR but no AMR‐GL. In contrast, the post‐transplant presence of C1q‐DSA was associated with significantly higher rates of AMR (86 vs 33 vs 0%; P < 0.001) and AMR‐GL (86 vs 0 vs 0%; log‐rank P < 0.001) compared with post‐transplant DSA without C1q‐binding or the absence of DSA. Patients with both pre‐transplant DSA and evidence of pre‐transplant T‐cell‐activation as indicated by soluble CD30‐positivity showed a significantly increased risk for AMR‐GL [HR = 11.1, 95% confidence interval (CI) = 1.68–73.4; log‐rank P = 0.013]. In these high‐risk patients, AMR‐GL was associated with total DSA in combination with T‐cell‐activation pre‐transplant, and de novo or persistent C1q‐binding DSA post‐transplant.